The Impact Information System Accounting And Information Technology - Sandag, Eltie Christi (Journal of Management, 2024)
Micro, Small, and Medium-Sized Businesses are critical to the economic development of a nation. MSMEs in the Bunaken Manado District have seen a number of difficulties and adjustments in recent years. One such issue is the poor level of financial literacy among these businesses, which results in a lack of knowledge of fundamental financial concepts like long-term planning, investing, and budgeting. having trouble implementing information technology because of access issues and a lack of knowledge about its advantages for improved operational and marketing effectiveness. The inefficiency of MSME financial management, especially the challenge of consistently producing accurate financial reports, prevents appropriate analysis and decision-making. Accounting information system use is crucial for enhancing MSMEs' performance since it facilitates the effective collection, management, and analysis of financial data. Quantitative approaches were used in this study. 324 MSMEs in Manado's Bunaken District made up the research sample; they were chosen through the use of a purposive sampling technique. Research data is tested with structural equation models using SmartPLS software. The study's findings indicate that, with a P value of 0.000, the use of accounting information systems and information systems has a positive and significant impact on MSMEs' performance, but financial literacy has no discernible impact at all (P = 0.103).